HIV EDUCATION AND STIGMATIZATION AMONG HIV PATIENTS IN NORTH CENTRAL NIGERIA - Bala, Nalah Augustine; Azman, Azlinda; Singh, Paramjit Singh Jamir (International Journal of Psychosocial Rehabilitation, 2020)
HIV education possed a social threat to adequate health care services and fueling HIV-related stigma and widespread HIV infection in North Central Nigeria. The inadequate knowledge of HIV/AIDS transmission hinders early diagnosis, antiretroviral treatment, and prevention of HIV/AIDS, thereby stimulating HIV stigma among HIV patients. The aim and objective of this study are to explore how HIV education can influence the stigmatization, health, and psychological well-being of the people diagnosed with HIV infection in North Central Nigeria. Twenty-five (25) participants male and females aged 18-62 years were selected through purposive sampling technique to participate in the study. We employed a qualitative study using in-depth interview and audio recorder for data collection, and thematic analysis using ATLAS.ti8 software for the transcription, coding, and analysis of data. The findings indicate that cultural values and religious beliefs influence the opportunity to acquire formal education and determine knowledge of HIV/AIDS. We, therefore, conclude that initiating collaborative behavioural-based intervention strategies of formal and non-formal education through a house-to-house HIV education program and public awareness campaigns can assist in enlightening the out-of-school population and their family members on the importance of Family Life HIV/AIDS Education. Also, the social support system and skills acquisition training for HIV positive and their family members who are not gainfully employed can reduce vulnerability to stigmatization and HIV transmission.